2014
DOI: 10.3109/02770903.2013.876647
|View full text |Cite
|
Sign up to set email alerts
|

IL-17A and IL-17F genes variants and susceptibility to childhood asthma in Tunisia

Abstract: Our results suggested that SNPs in IL-17A and IL-17F confer susceptibility to childhood asthma in Tunisia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
12

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 37 publications
0
28
0
12
Order By: Relevance
“…Omrane et al identified that rs2275913GG genotype could be considered as a protective factor against colon cancer (p=0.00001) with OR 3.77 (2.04-6.99) [18]. Maalmi et al observed a strong correlation between rs2275913G/A SNP and risk of asthma in Tunisian children [14]. Ocejo-Vinyals et al presented that rs2275913GG genotype was associated with increased susceptibility to pulmonary tuberculosis in northern Spain [17].…”
Section: Discussionmentioning
confidence: 96%
“…Omrane et al identified that rs2275913GG genotype could be considered as a protective factor against colon cancer (p=0.00001) with OR 3.77 (2.04-6.99) [18]. Maalmi et al observed a strong correlation between rs2275913G/A SNP and risk of asthma in Tunisian children [14]. Ocejo-Vinyals et al presented that rs2275913GG genotype was associated with increased susceptibility to pulmonary tuberculosis in northern Spain [17].…”
Section: Discussionmentioning
confidence: 96%
“…Multiple previous studies have reported an association between IL-17 gene polymorphisms and autoimmune diseases (Jin et al, 2011;Zhang et al, 2013;Maalmi et al, 2014;Shen et al, 2015). Jin et al (2011) reported an association between IL-17 gene polymorphisms and susceptibility to asthma in a Korean population, and suggested that the rs1889570 polymorphism was correlated with the development of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Shen et al (2015) reported that the IL-17 rs2275913 and rs3819024 variant alleles were associated with a decreased risk of rheumatoid arthritis, while the IL-17 rs3819025 and rs8193036 variant alleles were correlated with an increased risk of rheumatoid arthritis. Maalmi et al (2014) conducted a study in a Tunisian population, and found that the IL-17A rs2275913 and IL-17F rs763780 were associated with an increased risk of asthma in children. Zhang et al (2013) examined the association between IL-17 gene polymorphisms and inflammatory bowel disease, and reported that the IL-17 rs2275913 and rs763780 polymorphisms were associated with an increased risk of inflammatory bowel disease.…”
Section: Discussionmentioning
confidence: 99%
“…16 The SNP IL-17A G-152A has been reported to be associated with several different infections and diseases such as childhood asthma, pulmonary tuberculosis and colorectal cancer. 16,22,23 However, data are scarce about the effect of the IL-17A G-152A polymorphism on IL-17A production or pneumococcal colonization and infections. Previously, Lu et al 12 reported that immunization of mice with S. pneumoniae confers CD4+ T cell-dependent protection against colonization.…”
Section: Discussionmentioning
confidence: 97%